2006
DOI: 10.1063/1.2397074
|View full text |Cite
|
Sign up to set email alerts
|

Tracer diffusion in hard sphere fluids from molecular to hydrodynamic regimes

Abstract: Molecular dynamics is employed to investigate tracer diffusion in hard sphere fluids. Reduced densities (rho*=rhosigma(3), sigma is the diameter of bath fluid particles) ranging from 0.02 to 0.52 and tracers ranging in diameter from 0.125sigma to 16sigma are considered. Finite-size effects are found to pose a significant problem and can lead to seriously underestimated tracer diffusion constants even in systems that are very large by simulation standards. It is shown that this can be overcome by applying a sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
25
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 38 publications
1
25
0
Order By: Relevance
“…The dynamic properties of binary fluid systems where one particle species differs from the other only in size, mass or both of these parameters have been the subject of a large number of studies during the last years [1,2,3,4,5,6,7,8,9,10,11,12]. The increasing interest is, on the one hand, due to the fact that such systems serve as simple models for colloids and micellar solutions, which are of prime importance in many scientific areas such as biology or biochemistry, on the other hand it is sparked by the rapidly growing capabilities of modern computer hardware which allows us to investigate parameter ranges and system sizes that were not accessible before.…”
Section: Introductionmentioning
confidence: 99%
“…The dynamic properties of binary fluid systems where one particle species differs from the other only in size, mass or both of these parameters have been the subject of a large number of studies during the last years [1,2,3,4,5,6,7,8,9,10,11,12]. The increasing interest is, on the one hand, due to the fact that such systems serve as simple models for colloids and micellar solutions, which are of prime importance in many scientific areas such as biology or biochemistry, on the other hand it is sparked by the rapidly growing capabilities of modern computer hardware which allows us to investigate parameter ranges and system sizes that were not accessible before.…”
Section: Introductionmentioning
confidence: 99%
“…This fundamental phenomenon is of interest to many researchers of biology as well as physics [1][2][3][4][5][6][7][8]. In particular, one cannot disregard the friction from solvent particles when considering the dynamical functions of biomolecules [7].…”
Section: Introductionmentioning
confidence: 99%
“…To study the effect, many microscopic theories were previously developed [12,13]. When the solute particle is large, however, the theories are not suitable because of a finite-size effect [5]. We avoid this difficulty by employing a perturbation expansion, assuming that the ratio between the radii of the solvent and solute particles is a small perturbation parameter.…”
Section: Introductionmentioning
confidence: 99%
“…He concluded that for σ 2 /σ 1 > 1 the SE prediction is not valid for mass ratios 1/16 ≤ m 2 / m 1 ≤ 50, and that for σ 2 /σ 1 > 2 and for m 2 /m 1 < 1 the SE regime is reached for smaller densities than for the same system but m 2 /m 1 > 1. The test of SE formula for the size ratio or the mass ratio of the tracer was further discussed by Sokolovskii et al 8 for hard sphere fluids, by Cappelezzo et al 9 for Lennard-Jones (LJ) fluids, by Funazukuri et al 10 for supercritical and liquid conditions, and by Harris 11 for LJ, molecular, and ionic liquids.…”
mentioning
confidence: 99%
“…A time dependent friction coefficient ζ(t) is defined from the force autocorrelation function by 19 (8) and through the Laplace transforms of the projected and unprojected force autocorrelation functions, [14][15][16] in t space, the following relation is obtained .…”
mentioning
confidence: 99%